Human Trafficking: challenges and Opportunities for the 21st Century : Outcomes and Proposals - Jones, Jackie (Oñati Socio-Legal Series, 2018)
This contribution represents a synopsis of the discussions held over two days in plenary and groups at the Oñati International Institute for the Sociology of Law. The first group’s discussions centred on detailed recommendations for updating the EU Anti-Trafficking Directive with justifications from the expert groups as to the reasons for the changes, including a case study. The second group’s discussions focussed on a victim-centred approach to tackling human trafficking, outlining some of the key challenges and opportunities that could inform any changes to a new Anti-Trafficking Directive.